Ernst & Young's retirement planning guide - Arnone, William J....[et al] (John Wiley & Sons New YorkUS, 2001)
Advises on how to accumulate savings and investments for retirement. Discusses issues to be dealt with at retirement including: taxation, pension, and social security benefits. Examines choices and opportunities during retirement such as spending, investment and continuing health care provision. Provides guidelines for various retiree groups including: executives, the self-employed, women, and retirees in non-traditional families.